Broadband emission of Lu3Mg2GaSi2O12: Ce3+, Sm3+ phosphors and their potential application for w-LEDs. Issue 18 (15th September 2021) - Tang, He; Zhang, Xiyan; Cheng, Liqun; Xie, Jihuan; Yu, Xiaofang; Mi, Xiaoyun; Liu, Quansheng
Abstract: Herein, Lu3 Mg2 GaSi2 O12 : Ce 3+ /Sm 3+ (LMGS) phosphors with a garnet structure were synthesized by a high-temperature solid-phase reaction method, and their potential application in w-LEDs was evaluated. In this study, the crystal structure of the phosphor was determined using the Rietveld method and XRD pattern analysis, while the luminescence performance was characterized by the relevant PL spectrum, and then, the energy transfer (ET) mechanism was explored. When subjected to an excitation at a wavelength of 450 nm, the introduction of Sm 3+ ions into LMGS: 0.015Ce 3+ broadens the broadband emission of Ce 3+ ions owing to the co-excitation and ET of Ce 3+ and Sm 3+ . A continuous and controlled variation in the Sm 3+ doping concentration facilitates the tuning of color coordinate from green to yellow. The maximum Ce 3+ →Sm 3+ energy transfer efficiency of the sample was 55.64 %. From the viewpoint of practical applications, the sample exhibited excellent thermal stability and water resistance. After combining the LMGS: 0.015Ce 3+, 0.03Sm 3+ sample with a commercial red phosphor and a blue chip, a warm white LED with a color rendering index of 86.6 and color temperature of 3592 K can be obtained.